The Impacts Information Technology On Business - Moses Isdory Mgunda (Journal of International Conference Proceedings (JICP), 2019)
Information Technology (IT) is among the relevant factor assisting the business to penetrate in a new market for being innovative and generating new product and services which help the growth of the business and company. The revolution of IT and internet facilitates the outstanding performance of the economy in business sector, through the exchanges of information by using internet and electronic devices facilitate accessibility of doing business between companies globally. This study tries to analyse the impact of IT on business and the performance of the economy. The empirical findings show that the role of IT in business is tremendous.